SUPPLY CHAIN RESILIENCE AND BUSINESS CONTINUITY IN INDONESIAN MANUFACTURING SECTOR - Nia Riana; Arif Budi Raharja; Ijang Faisal (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Background: COVID-19 pandemic exposed vulnerabilities in global supply chains, prompting Indonesian manufacturers to reassess resilience strategies. Aims: This study examines supply chain resilience practices and their impact on business continuity in Indonesian manufacturing sector. Research Method: Mixed-methods approach combining surveys of 156 manufacturing companies with case studies of 12 high-resilience organizations across diverse industries. Results and Conclusion: Companies with diversified supplier bases, digital supply chain visibility, and flexible production capabilities demonstrated 64 percent faster disruption recovery. However, only 38 percent of surveyed companies implemented comprehensive resilience strategies. Supplier relationship quality and information sharing emerged as critical enablers. Contribution: Research provides framework for Indonesian manufacturers to enhance supply chain resilience through strategic supplier management, technology adoption, and contingency planning.